2013
DOI: 10.1124/mol.113.087940
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Induces Mitochondrial Injury by Inhibiting Ferrochelatase Heme Biosynthesis Activity

Abstract: Salicylic acid is a classic nonsteroidal anti-inflammatory drug. Although salicylic acid also induces mitochondrial injury, the mechanism of its antimitochondrial activity is not well understood. In this study, by using a one-step affinity purification scheme with salicylic acid-immobilized beads, ferrochelatase (FECH), a homodimeric enzyme involved in heme biosynthesis in mitochondria, was identified as a new molecular target of salicylic acid. Moreover, the cocrystal structure of the FECHsalicylic acid compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…F Phosphorylation of eIF2a at Ser51 and protein levels of Hsp90 were measured by immunoblot after knocking down FECH in HRECs. There are also prospects for novel FECH inhibitors as therapy: We have developed cremastranone analogs that may also act through FECH (Basavarajappa et al, 2015), and recently, the drugs vemurafenib (Savitski et al, 2014) and salicylic acid (Gupta et al, 2013), as well as a lipid-derived probe compound (Niphakis et al, 2015), were all shown to bind to FECH, suggesting that this protein has many potential binding clefts and is therefore likely druggable with novel compounds. FECH is the only known enzyme in humans to synthesize heme, and any loss of activity of this enzyme might result in intracellular heme deficiency (Dailey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…F Phosphorylation of eIF2a at Ser51 and protein levels of Hsp90 were measured by immunoblot after knocking down FECH in HRECs. There are also prospects for novel FECH inhibitors as therapy: We have developed cremastranone analogs that may also act through FECH (Basavarajappa et al, 2015), and recently, the drugs vemurafenib (Savitski et al, 2014) and salicylic acid (Gupta et al, 2013), as well as a lipid-derived probe compound (Niphakis et al, 2015), were all shown to bind to FECH, suggesting that this protein has many potential binding clefts and is therefore likely druggable with novel compounds. FECH is the only known enzyme in humans to synthesize heme, and any loss of activity of this enzyme might result in intracellular heme deficiency (Dailey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin is currently being used as a preventive medication for colorectal cancer, though the mechanism is not fully understood. Recently, it was shown that the mechanism of action of aspirin and particularly salicylic acid as an anti‐mitochondrial and anti‐inflammatory agent requires the presence of wild type FECH . Moreover, FECH mRNA expression was shown to be down‐regulated in brain glioma tissues .…”
Section: Discussionmentioning
confidence: 99%
“…1). Metformin and aspirin are toxic at high doses, and results with the combination could reflect convergence on a common mechanism such as mitochondrial function (see El Mir et al 2000;Gupta et al 2013). The fact that metformin largely masked the impacts of aspirin suggests that a lower dose of metformin might obtain greater benefits.…”
Section: Discussionmentioning
confidence: 99%